2015
DOI: 10.1108/scm-03-2014-0090
|View full text |Cite
|
Sign up to set email alerts
|

Resource-efficient supply chains: a research framework, literature review and research agenda

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 154 publications
4
44
0
1
Order By: Relevance
“…Managers should gather information and collaborate closely with suppliers in order to find where scarce natural resources appear in their products and operations. This is in line with Matopoulos et al (2015) who suggested the "resource awareness" requirements of supply chains. This study shows that when it comes to resource scarcity implications, suppliers could be playing a more proactive role influencing the smooth functioning of the supply chain.…”
Section: Managerial and Policy Implicationssupporting
confidence: 88%
“…Managers should gather information and collaborate closely with suppliers in order to find where scarce natural resources appear in their products and operations. This is in line with Matopoulos et al (2015) who suggested the "resource awareness" requirements of supply chains. This study shows that when it comes to resource scarcity implications, suppliers could be playing a more proactive role influencing the smooth functioning of the supply chain.…”
Section: Managerial and Policy Implicationssupporting
confidence: 88%
“…Bell et al, 2013;Lapko et al, 2016), these efforts come with shortcomings and gaps. For example, in the research by Bell et al (2012;; Matopoulos et al, (2015); Kalaitzi et al, (2018) the links among supply chain strategies, resource efficiency and competitive advantage lacked empirical validation. In general, research on the impact of supply chain strategies on organisational performance and particularly on resource efficiency and competitive advantage is scant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing awareness about climate change in the community has the potential to alter consumer perceptions about what they value in a food product as well as what new product offerings would be attractive. On this basis, the field of sustainable supply chain management has emerged and has grown in importance over the past decade [31][32][33], adding to the well-established practice of supply chain risk assessment [34], although neither of these fields yet address climate adaptation in any comprehensive way [35].…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle assessment (LCA) [36,37] is widely used to assess resource use and environmental impacts along supply chains; however its technical complexity can act as an obstacle to implementation in many business contexts, the results are often influenced strongly by modelling choices and parameter settings, and the technique is rarely used in a combinative way with other analytical and decision support tools [32,38]. As such, LCA is relatively underutilized in sustainable supply chain management [31].…”
Section: Introductionmentioning
confidence: 99%